CAREER DIRECTION OF YOUNG PEOPLE FROM BIG AND SMALL RUSSIAN CITIES - E. Yu. Cherniakevich (Publishing House of the State University of Management, 2020)
The results of a study of the career orientation of university students from large and small Russian cities have been described. To conduct the study, methods were used to identify leading career orientations, the level of motivation for a career, career self-efficacy, and the projective method of “unfinished offers” was used. The differences in the career orientations of students have been presented, the features of self-efficacy, career motivation and individual ideas about it have been revealed. It has been concluded that students from large and small cities are not aimed at developing their professional competence, first of all, they are focused on “autonomy”, “management” and “stability of work”. There are significant differences in career orientations: students from big cities are more focused on “service” and “integration of life styles”. The indicators of career motivation and self-efficacy of students from small and large cities are similar and correspond to the average level. The perceptions of students from small towns about a career have both positive and negative connotations, in contrast to students from large cities who do not note a negative attitude towards career.